Epicardial adipose tissue and right ventricular dysfunction in patients with acute pulmonary embolism - Staśkiewicz, Grzegorz; Piech, Piotr; Siek, Elżbieta; Przybylski, Piotr; Baj, Jacek; Olechowski, Piotr; Maciejewski, Ryszard; Czekajska-Chehab, Elżbieta; Drop, Andrzej (Journal of Education, Health and Sport, 2019)
Epicardial adipose tissue has been linked with increased cardiovascular morbidity. Its correlation with right ventriclar morphology and physiology is a recent concept. The aim of the study was to analyze severity of right ventricular dysfunction in the course of acute pulmonary embolism with the amount of epicardial adipose tissue. Retrospective analsis of 192 computed tomography studies with confirmed pulmonary embolism was performed. Patients were divided into two groups with low and high amount of epicardial adipose tissue. Although no significant differences of BMI and severity of pulmonary embolism were observed between the groups, in patients with high amount of epicardial fat, right ventricular dysfunction was significantly more severe.